Explaining sectoral discrepancies between national and provincial statistics in China - Ma, Ben; Song, Guojun; Zhang, Lei; Sonnenfeld, David A. (China economic review, 2014)
This paper examines sectoral contributions to discrepancies between China's national aggregate statistical values and the sum of provincial figures. In institutional terms, the paper then explores the sources of principally sectoral discrepancies. We find that the industrial sector has been the major contributor to discrepancies in both gross domestic product (GDP) and total energy consumption in recent years. Technical aspects such as statistical coverage, data collection method, and double-counting cannot explain the discrepancy. For the industrial sector, limited data accessibility undermines external checks and balances from the general public. As the primary bodies in collecting industrial data, the Provincial Bureaus of Statistics (PBSs) are not subject to effective internal checks and balances from other governmental divisions. To out-compete counterparts and get promoted, provincial leaders have explicit incentives to overstate provincial GDP, with industrial added value being the first statistic to be affected. This dynamic further extends to industrial energy consumption, which is over-reported as well. •This paper examines institutional causes of data discrepancies in Chinese statistics.•Discrepancies in GDP and energy consumption are mainly from the industrial sector.•Institutional arrangements are the main causes rather than technical aspects.•To get promoted, local officials have explicit incentive to exaggerate local data.•Ineffective constraints give rise to the largest discrepancy in industrial sector.